Konsep Kritik Matan dalam Pelestarian Otentisitas Hadis - Ilmi, Nur; Tangngareng, Tasmin; Farhah, Ummi (CV Kalimasada Group, 2024)
This article focuses on the concept of hadith text criticism, which is essential to understand when evaluating hadiths. It covers the history, objectives, benefits, and steps involved in the process of text criticism. The method employed is library research using a deductive-inductive analytical approach to assess the quality of a hadith, ensuring its authenticity is undisputed when practiced. The research findings reveal that both sanad (chain of narration) and matan (text) criticism have been in practice since the time of the Prophet Muhammad (peace be upon him). This practice was carried out by his companions, the tabi’in, the tabi’-tabi’in, and hadith scholars up to the present day. Text criticism is particularly important to determine whether a hadith's matan is authentic or not. If the matan is found to be unauthentic, the hadith cannot be used as a basis for religious matters.